Factors influencing difficult and failed intubation in patients undergoing gynecologic oncology surgery: a retrospective cohort study - Kına, Seyyid Furkan; Koç, Zeynep; Usalan, Damla; Sezgi, Atakan; Altınsoy, Savaş; Ergil, Julide (The European Research Journal, 2025)
Objectives: Difficult and unsuccessful intubation is a leading cause of anesthesia-related morbidity and mortality. This study aimed to investigate the incidence and contributing factors of difficult and unsuccessful intubation in patients undergoing gynecologic oncology surgery, particularly those with significant comorbidities and obesity. Methods: The study included 653 patients over 18 years of age who underwent gynecologic oncology surgery with planned intubation under general anesthesia between January 1 and July 1, 2024. Data collected included demographic information, number of intubation attempts, personnel involved in intubation, auxiliary methods employed, intubation duration, complications, mouth opening, sternomental distance, thyromental distance, neck mobility, upper lip bite test results, presence of retrognathia or micrognathia, obstructive sleep apnea, and mobile dentures. Results: The incidence of difficult intubation in our cohort was 7.5%, with no cases of failed intubation. Significant factors associated with increased risk of difficult intubation included body mass index (P=0.008), obstructive sleep apnea (P